Conversion Disorder in a Pharmacogenomics, Polypharmacy Patient: Case Report - Michael J. Schuh (University of Minnesota Libraries Publishing, 2021)
Background: Conversion disorder (CD) is a relatively common psychiatric disorder likely encountered by clinical pharmacists but probably not easily identified by pharmacists.